THE EFFECTS OF TEACHING NARRATIVE TEXT BY WATCHING ANIMATION VIDEO AND MIND MAPPING ON THE STUDENTS’ WRITING SKILL AT SMP MUHAMMADIYAH PALANGKARAYA - Masruroh, Binti (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2021)
The research is conducted in order to see the effects of the students’ ability in writing narrative text after watching movie and using mind mapping. The population of this research was the eighth grade students of SMP Muhammadiyah Palangka Raya in academic year 2015/2016. The number of sample was thirty students. The research design was quasi experimental and there were two groups those who were taught by using Animation movie and by using mind mapping. The data were analyzed by using Paired Sample T Test by IBM SPSS Version 22. The significant value of the data of post-test in the Experimental Group by using Animation Movie was 0.013; as 0.013 < 0,05 Ha then was accepted. The significant value of the data of post-test in the Experimental Group by using Mind Mapping was 0.012; as 0.012 < 0,05 then Ha was accepted. In both Experimental Group by using movie and mind mapping the significant value for post test was 0.014; as 0.014 < 0.05 then Ha was accepted. Therefore, at the significant level of 0.05, there is a significant effect on the ability of the students in writing narrative text after watching movie and using mind mapping.